STUDI KEPUSTAKAAN TENTANG PEMBELAJARAN PASING BAWAH PADA SISWA SEKOLAH MENENGAH PERTAMA - Michael Johannes Hadiwijaya Louk; Riswandi Timuneno; Arly Elizabeth Maria de Haan (Nusa Cendana University, 2021)
The purpose of this study was to determine the lower level of learning in the students of SMP Negeri 3 Amarasi Barat. The subject of this research is to find out the low-passing learning of the students of SMP Negeri 3 Amarasi Barat. The location of this research is SMP Negeri 3 Amarasi Barat, Kupang Regency. Lower pasing learning is a process of learning the lower pass movement skills in volleyball with the correct techniques in accordance with the desired expectations. The method used in this research is descriptive with a qualitative approach. The instrument used in this study was in the form of documentation guidelines, based on the findings obtained by researchers in the field, students did not understand and did not understand how to do good and correct passing down: 1. Where the body posture is not as good or both legs not opened shoulder width apart so that when picking up the ball the ball does not bounce properly, 2. Both hands are not extended forward or both hands are not straightened forward so that when picking up the ball, the ball does not bounce properly or when returning the ball is not on the intended target, 3. Hands are not held together when taking the ball, 4. Do not focus on the ball so that when taking and returning the ball it is not directed at the intended target. It can be concluded that the good and correct bottom line in the lesson plan (RPP) is to provide knowledge and insight into the literature study of the lower level volleyball learning at SMP Negeri 3 Amarasi Barat.